(3QSGdI aj GdMLL GdYTQIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3dh WQb GdYGbd Edi UQa GdeYQha Yf GdeYGQa NUhUkG EPG cGf GdeYQha CaVd YUeg jJeSc HgG ef SYO HGdMjGI s
(3BNQgG (B:s
(3hJQZH ai GdZHWI GdGHOjI hJbHd fUjMI CNjc hhdjc hJJQc GdEZJQGA HRNGQa GdOGQ hJbHd Ydi cSH NjQGJ GdOGQ GdEdgjI Cbhd bhdi gPG hCSCd Gddg Cf jQTOc deG CQi JMjI ajc HaVdg hEMSGfg Efg hdi Pdc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs